An Investigation of the Impact of Jagged Profile on L2 Speaking Test Ratings: Evidence from Rating and Eye-tracking Data. Issue 4 (8th August 2022) - Ma, Wenyue; Winke, Paula
ABSTRACT: The factors that influence rater scoring have been a subject of great interest to researchers in second language assessment. However, the research on the impact of test-takers' speech profiles (e.g., a jagged or a flat profile reflecting analytic subscores) on raters' scoring behaviors remains to be seen. To investigate the role of speech profiles in scoring, we collected analytic and holistic rating scores from 28 trained raters while they were marking the performances of three groups of speakers with distinct profiles, determined by prior ratings. We tracked eleven of the raters' eye-movements to record how often and how long they looked at the various categories on the rating scales. We found that the raters perceived speakers who have better pronunciation as overall more competent speakers. Meanwhile, speakers' score profiles influenced raters' attention: raters fixated longer and more often, and made more eye-visits, to the lexical grammar category while assessing speakers with a jagged profile. Raters spent less time assessing the pronunciation of the speakers who were pre-identified as having better pronunciation. The findings shed light on the impact of speech characteristics on raters' cognition and score assignments and therefore have important implications for rater training in L2 speaking assessments.